Making Data Analysis into Incentive Compatibility Mode Using DNCC Approach - K Lavanya2, P Vamsi Naidu1 , (International Journal of Scientific Research and Management (IJSRM), 2015)
Generally the organizations wanted to conduct data analysis on their private data in order to getting betterpredictions for their benefits .Even though we have some Privacy Preserving Data Analysis (PPDA) techniques that are notsure about the participating parties are true about their input or not. This leads one organization may confidentially breachthe other organizations data and misuses it. This misuse leads severe harm to the organization which lost its information. Thispoint raises a question of how to design PPDA techniques that motivates participating parties to provide truthful inputs. In thispaper we clearly see the current approaches that are being in use and proposing a new methodology called DNCC and its wayworking and we will see how this approach makes the data analysis into incentive compatible